Passion and Power: Sexuality in History - Maynard, Steven (Labour / Le Travail, 1991)
The article reviews the book, "Passion and Power: Sexuality in History," edited by Kathy Peiss and Christina Simmons.
Keywords: BOOKS -- Reviews; HUMAN sexuality & history; Nonfiction; PASSION & Power: Sexuality in History (Book); PEISS, Kathy; SIMMONS, Christina